Practical water - Hillman, Brenda (Wesleyan poetry., 2009)
Practical Water is, like Brenda Hillman's previous two books, Cascadia and Pieces of Air in the Epic, both an elemental meditation and an ecopoetics; this time her subject is water: Taoist water, baptismal water, water from the muses' fountains, the practical waters of hydrology from which we draw our being -- and the stilled water in a glass in a Senate chamber. Not since Allen Ginsberg tried to levitate the Pentagon has American poetry seen the likes of the hallucinatory wit and moral clarity that Hillman brings to Washington in her poems about Congressional Hearings on the Iraq War. Here also -- because it is about many kinds of power -- is a sequence of twinned lyrics for the moon, governess of tides and night vision, for visible and invisible faces. Violence and the common world, fact and dream, science and magic, intuition and perception are reconfigured as the poet explores matters of spirit in political life and earthly fate. If it is time to weep by the waters of Babylon, it is also time to touch water's living currents. No one is reimagining the possibilities of lyric poetry with more inventiveness; this is masterful work by one of our finest poets -- Publisher.